Development of Speech and Communication of the Child with Autism Spectrum Disorder: A Case Study - Syta, Aneta (Logopedia Silesiana, 2018)
The aim of the article is to show the degree of speech development of a 6-year-old boy diagnosed with autism. The article also presents, among others, the development of the child’s motor skills, medical documentation, and the results of specialist research. Finally, the proposal of a speech therapy plan is presented, and the need to work on accompanying disorders is emphasised.